Faktor keberhasilan ibu pekerja dalam memberikan ASI eksklusif di Puskesmas Sedayu I, Bantul, Yogyakarta - Fania Fitriani; Wahyuningsih Wahyuningsih; Kayat Haryani (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTBackground: Breastmilk is the first food and the best food for the baby. Breastmilk contains variety of nutrients needed for the baby. It is important to identify the success factors in giving exclusive breastfeeding Objectives: To obtain deeper understanding about factors that determine the success of carrier women in giving exclusive breastfeed ing in Puskesmas Sedayu II, Bantul, Yogyakarta Methods: This research used qualitative study design with phenomenological approach. There were five participants in this study, who lived near Puskesmas Sedayu II, Bantul, Yogyakarta. The participant aged 27-32 years and had children aged 6-12 months. The education background of participants were high school until under graduate study. Participants worked as private employees and healthworkers in private hospitals in Yogyakarta.Results: Partisipants understood about the importance of exclusive breastfeeding, the trusted in breastmilk production, concern with nutrition intake during breastfeed, and had the support from closed people to give exclusive breastfeeding.Conclusions: Factors that determine the success of working mothers in giving exclusive breastfeeding include: understanding of participants about giving exclusive breastfeeding, trusting in the breastmilk production, concerning in nutrition intake during breastfeed, and supporting from people closed people to give exclusive breastfeeding.KEYWORDS: exclusive breastfeeding, success factors, supportABSTRAKLatar belakang: ASI merupakan makanan yang pertama dan terbaik bagi bayi. ASI mengandung berbagai zat gizi yang dibutuhkan bagi bayi, sehingga penting untuk mengidentifi kasikan faktor keberhasilan dalam pemberian ASI eksklusif.Tujuan: Untuk mendapatkan pemahaman yang mendalam tentang faktor keberhasilan ibu pekerja dalam memberikan ASI eksklusif di Puskesmas Sedayu II, Bantul, Yogyakarta.Metode: Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Partisipan penelitian berjumlah 5 yang bertempat tinggal di wilayah kerja Puskesmas Sedayu II, Bantul, Yogyakarta dengan karakteristik partisipan usia 27-32 tahun dan mempunyai anak usia 6-12 bulan. Pendidikan partisipan yaitu SMK hingga S1. Pekerjaan partisipan sebagai karyawan swasta dan tenaga kesehatan di RS swasta di Yogyakarta.Hasil: Ibu memahami tentang pentingnya ASI eksklusif, yakin terhadap produksi ASI, memperhatikan asupan gizi selama menyusui, dan mendapat dukungan orang terdekat untuk memberikan ASI eksklusif. Kesimpulan: Faktor keberhasilan ibu bekerja memberikan ASI ekslusif meliputi: pemahaman ibu tentang pentingnya ASI eksklusif, keyakinan terhadap produksi ASI, memperhatikan asupan gizi selama menyusui, dan dukungan orang terdekat terhadap pemberian ASI eksklusif. KATA KUNCI: ASI eksklusif, faktor keberhasilan, dukungan orang terdekat